Feasibility study of generating mechatronic devices by digital direct metallization with a plasma based copper coating process - Müller, Martin; Franke, Jörg (Proceedings of the International Spring Seminar on Electronics Technology, 2016)
Digital Direct Metallization (DDM) is an innovative process for the production of planar or three dimensional circuit carriers. Both conductor lines for logic circuits and conductors for high power transmissions can be realized. This paper describes the manufacturing process chain of Digital Direct Metallization by plasma based copper coating and shows the potentials of this technology. Circuits can be applied to almost any base substrate such as polymers, ceramics or even metal since an insulating dielectric lacquer layer separates the substrate from the metallization. In contrast to previous plasma based copper depositing processes the Digital Direct Metallization enables clearly defined fine structures without using any inflexible and high-maintenance masks [1]. An enormous advantage of this procedure is the complete elimination of wet chemical process steps, which are known from the laser direct structuring method (LDS) [2]. In addition to diverse mechanical and electrical characterizations this paper represents the opportunities of the technology by means of a demonstrator application.
CRIS-Team Scopus Importer:2023-03-07